FACULTY AWARENESS ON THE COLLECTION DEVELOPMENT OF THE INTERNATIONAL ISLAMIC UNIVERSITY LIBRARY - Abdul Rahman, Mohd Zain; Darus, Siti Hawa (Malaysian Journal of Library and Information Science, 2004)
This study investigates the faculty awareness on the collection development of the International Islamic University Malaysia (IIUM) Library among faculty members of the Kulliyyah of Islamic Revealed Knowledge and Human Science (KIRKHS) IIUM, as well as issues that affect this awareness. The study is able to demonstrate the faculty participation in the collection development of the library, thus bring forward some recommendations that might be useful for the library to further improve its services.